Impingement and loosening of the long posterior wall acetabular implant. - Murray, D (1992)
Long posterior wall (LPW) Charnley acetabular implants are widely used as it is believed that the LPW helps to prevent dislocation. This has, however, not been proven statistically. In a preliminary study of these implants removed at revision marked erosion of the LPW was frequently seen, indicating that repetitive impingement may occur. The influence of the long posterior wall was therefore investigated mathematically. LPW and standard sockets were found to be equally likely to dislocate provided that the standard socket was anteverted 5 degrees more than the LPW socket. With simulated external rotation, LPW sockets impinge 30% earlier than standard sockets. When impingement occurs a torque is applied to the components, which increases the shear stresses at the cement-bone interface. The torques, although not large enough to dislodge the socket immediately, are repetitive and so may contribute to loosening. The LPW socket can generate twice as much torque as the standard socket and therefore is more likely to loosen.